Androgen deprivation and high-dose radiotherapy for oligometastatic prostate cancer patients with less than five regional and/or distant metastases. (November 2013) - Schick, Ulrike; Jorcano, Sandra; Nouet, Philippe; Rouzaud, Michel; Vees, Hansjoerg; Zilli, Thomas; Ratib, Osman; Weber, Damien C.; Miralbell, Raymond
Abstract Background. Substantial survival may be observed with oligometastatic prostate cancer. Combining androgen deprivation (AD) and high-dose external beam radiotherapy (RT) to isolated regional or distant lesions may be proposed for these patients and the outcome of this strategy is the purpose of the present report. Material and methods. From 2003 to 2010, 50 prostate cancer patients were diagnosed with synchronous (n = 7) or metachronous (n = 43) oligometastases (OM). Among the relapsing patients, the recurrence occurred after radical prostatectomy in 33 patients and curative RT (± AD) in 10 patients. The median age at diagnosis was 63 years (range, 48–82). All patients underwent a bone scan and 18F-choline or 11C-acetate PET-CT at the time of diagnosis or relapse, showing regional and/or distant nodal and bone and/or visceral metastases in 33 and 17 patients, respectively. The median delivered effective dose was 64 Gy. All but one patient received neo-adjuvant and concomitant AD. Results. After a median follow-up of 31 months (range, 9–89) the three-year biochemical relapse-free survival (bRFS), clinical failure-free survival, and overall survival rates were 54.5%, 58.6% and 92%, respectively. No grade 3 toxicity was observed. Improved bRFS was found to be significantly associated with the number of OM. The three-year bRFS was 66.5% versus 36.4% for patients with 1 and > 1 OMs (p = 0.031). A normalised total dose (NTD in 2 Gy/fraction, alpha/beta = 2 Gy) above 64 Gy was also correlated with a better three-year bRFS compared to lower doses: 65% vs. 41.8%, respectively (p = 0.005). On multivariate analysis, only the NTD > 64 Gy retained statistical significance (HR: 0.37, 95% CI 0.15–0.93). Conclusion. Oligometastatic patients may be successfully treated with short AD and high-dose irradiation to the metastatic lesions. High dose improves bRFS. Such a treatment strategy may hypothetically succeed to prolong the failure-free interval between two consecutive AD courses.